(untitled) (Journal of Guidance and Counselling Studies, 2022)
The study sought to determine counselling strategies for preventing social vices among secondary school students in Rivers State. Two research questions guided the study. The study adopted a descriptive research design. The area of the study was Rivers State. The Population of the study was 60 practising school Counsellors in public secondary schools in Rivers State. A total of 55 questionnaires were returned by school Counsellors. There was no sampling as the total of 55 respondents was studied. The instrument for data collection was a researcher-structured questionnaire based on modified four-point scales of Strongly Agree, Agree, Disagree and Strongly Disagree. The instrument contained a total of 15 items and divided into sections A and B. The questionnaire had an internal consistency reliability estimate yielded 0.72 for Cluster A; 0.66 for Cluster B; which give 0.69 in averages. The data collected were analyzed using mean, for the responses of the research questions, items with mean score of 2.50 and above were regarded as agreement while items with less than 2.50 were regarded as disagreement. Findings from the study revealed that some Secondary school students are now members of a secret cult in school, Secondary schools students now involved in online gambling and sport betting, Secondary school students engaging in pre-marital sexual relationship are the various forms of social vices exhibited by Secondary school students among others. Recommendations were made that Parents should equally make themselves available at home to train their children and stop leaving them in the hands of nannies, house boys/ maids and teachers.